Mapping the spatial distribution of nocturnal urban heat island based on Local Climate Zone framework - Zheng, Yingsheng (2023)
A spatial understanding of street-scale urban heat island (UHI) is essential but challenging in Hong Kong, due to its highly heterogeneous urban environment and a limited weather station monitoring network. Night-time mobile measurements were conducted during the summertime of 2014 to monitor UHI variation at local level. Three measurement routes and a total of 80 sample sites were selected according to the Local Climate Zone (LCZ) framework. The measured climatic data and urban morphology data were synergized and analyzed at LCZ scale through Geographical Information System (GIS). Stepwise Multiple Linear Regression (MLR) and Partial Least Square Regression (PLSR) were applied to quantify the connections between urban form and local UHI conditions of LCZ. Mean sky view factor, total street length, and pervious surface fraction of LCZ sites have been found to be the most explanatory variables of local UHI intensity, and over 50% of UHI variations can be explained by both statistical models of stepwise MLR and PLSR. An UHI evaluation map of urban areas in Hong Kong has been developed based on the statistical models, through which UHI hotspots have been identified. LCZ-based UHI mitigation strategies were further developed for climatic planning of Outline Zoning Plan areas. The results indicate that urban forms have significant influences on UHI development at local scale, and an optimal design of urban morphology is necessary for UHI mitigation and climate adaptation.